Elemental composition of Miscanthus biomass grown on different kinds of Technosols - Kharytonov, Mykola; Харитонов, Микола Миколайович; Babenko, Mykhailo; Бабенко, Михайло; Martynova, Nadia; Мартинова, Надія; Klimkina, Iryna; Клімкіна, Ірина; Wiche, Oliver; Віче, Олівер; Heilmeier, Hermann; Хайльмаєр, Герман (Routledge, частина Taylor & Francis Group, 2023)
Miscanthus has been grown on four kinds of Technosols. These soil materials have relatively low levels of macronutrients and imperfect nutrient balance. Even so, miscanthus is able to produce substantial, stable yields from the third year of cultivation. The poorest yields were obtained on dark-grey schist clay; the highest on loess-like loam and red-brown clay. Miscanthus actively accumulates macronutrients, especially sulphur, whereas sodium and magnesium are accumulated in the smallest amounts; potassium and phosphorus are mainly accumulated in the stems, calcium and sulphur in the leaves. Міскантус вирощували на чотирьох видах Техноземів. Ці ґрунти матеріали мають відносно низький рівень макроелементів і незбалансоване співвідношення поживних речовин. Незважаючи на це, міскантус здатний виробляти значні, стабільні врожаї з третього року вирощування. Найменші виноси отримані на темно-сірій сланцевій глині; найвищі - на лесоподібних суглинок і червоно-бура глина. Міскантус активно накопичує макроелементи, особливо сірку, тоді як натрій і магній накопичуються в найменших кількостях; калій і фосфор в основному накопичується в стеблах, кальцій і сірка в листі.
Елементний склад біомаси міскантусу вирощеного на різних видах техноземів
Keywords: Technosols; техноземи; miscanthus; міскантус; biomass; біомаса; elementary accumulation; акумуляція елементів